ORGANIZATIONAL COMMUNICATIONS - Anggraini, Siti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2007)
To be able to indentify characters of an organization indicative of healthy status.To understand techniques designed to facilitate communications in complex organizational structures